2014
DOI: 10.1021/ac5003905
|View full text |Cite
|
Sign up to set email alerts
|

Polydopamine-Functionalization of Graphene Oxide to Enable Dual Signal Amplification for Sensitive Surface Plasmon Resonance Imaging Detection of Biomarker

Abstract: Surface plasmon resonance imaging (SPRi) is one of the powerful tools for immunoassays with advantages of label-free, real-time, and high-throughput; however, it often suffers from limited sensitivity. Herein we report a dual signal amplification strategy utilizing polydopamine (PDA) functionalization of reduced graphene oxide (PDA-rGO) nanosheets for sensitive SPRi immunoassay in serum. The PDA-rGO nanosheet is synthesized by oxidative polymerization of dopamine in a gentle alkaline solution in the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 127 publications
(65 citation statements)
references
References 31 publications
(68 reference statements)
1
64
0
Order By: Relevance
“…The strong absorption peak located at 1620 cm −1 indicated the existence of CC. The peak located at 1300 cm −1 was due to the stretching vibrations of CN groups in the PDADs . Similarly, the 1 H‐NMR and 13 C‐NMR spectra of the PDADs are shown in Figure (d,e).…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…The strong absorption peak located at 1620 cm −1 indicated the existence of CC. The peak located at 1300 cm −1 was due to the stretching vibrations of CN groups in the PDADs . Similarly, the 1 H‐NMR and 13 C‐NMR spectra of the PDADs are shown in Figure (d,e).…”
Section: Resultsmentioning
confidence: 77%
“…The Stokes shift and full width at half‐maximum of the PDADs were 164 and 80 nm (20 nm), respectively. This indicated that the PDADs had a weak self‐absorption effect and low energy loss . Moreover, the narrowing of the full width at half‐maximum (which was much smaller than that of graphene quantum dots, carbon dots, or polymer dots) also indicated unified chromophores in the PDADs .…”
Section: Resultsmentioning
confidence: 99%
“…Such sensors have been used for the sensitive detection of hydrogen peroxide phenolic compounds, catechol alcohols, glucose and the folate receptor from complex, biological samples. The biocompatible binding of proteins has also been used for the attachment of antibodies to surfaces to construct a number immunosensors with colorimetric, chemiluminescence, electrochemical, photoelectrochemical, and plasmon resonance detection …”
Section: Applications Of Catecholamine Polymersmentioning
confidence: 99%
“…This material can be oxidized and deposited spontaneously on different surfaces as a uniform layer of polydopamine (PDA) which is named self‐polymerization process. The self‐polymerized dopamine on the GO surface has been utilized to reusable adsorbents for water purification, imaging detection of biomarker, hydroxyapatite mineralization, the adsorption of organic dyes and heavy metal ions . Moreover, RGO‐PDA can be used as initial material of three component nanocomposites including nanometals which have some applications in divers' fields.…”
Section: Introductionmentioning
confidence: 99%